2016
DOI: 10.1111/rda.12860
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of the canine sperm plasma membrane as markers of sperm motility

Abstract: ContentsThe fatty acid composition of the sperm membrane is an important factor involved in the overall sperm quality, including motility. However, in the canine species, the exact composition of the plasma membrane is still unknown. Therefore, the purpose of this study was to evaluate the plasma membrane lipid composition of motile sperm cells and to compare it with asthenospermic samples, as an attempt to determine possible involvements of membrane lipids in dog sperm cell motility. The sperm-rich fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
2
33
0
6
Order By: Relevance
“…Since the lipid composition of the sperm plasma membrane is a major determinant of sperm motility [ 91 ], we expected to observe changes in sperm motility with the incorporation of exogenous GPL. To test this hypothesis and get functional data on the incorporation of GPL from the sub-μm-sized micelles into sperm membranes, we measured the motility of human sperm with Computer Assisted Sperm Analysis (CASA) after incubation of various concentrations of sub-μm-sized micelles made with different concentrations of GPL.…”
Section: Resultsmentioning
confidence: 99%
“…Since the lipid composition of the sperm plasma membrane is a major determinant of sperm motility [ 91 ], we expected to observe changes in sperm motility with the incorporation of exogenous GPL. To test this hypothesis and get functional data on the incorporation of GPL from the sub-μm-sized micelles into sperm membranes, we measured the motility of human sperm with Computer Assisted Sperm Analysis (CASA) after incubation of various concentrations of sub-μm-sized micelles made with different concentrations of GPL.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid composition of the plasma membrane (cholesterol and unsaturated fatty acids) is directly related to the motility of the sperm and the fluidity of the membrane; the presence of unsaturated fatty acids gives the membrane greater fluidity. Lucio et al (2017) have reported the presence of both saturated (palmitic and stearic) and unsaturated fatty acids (arachidonic and oleic) in dog spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol stiffens the sperm plasma membrane and makes it more permeable for different molecules and compounds. Unfortunately, the presence of double bonds increases the chemical reactivity, which may lead to the loss of motility and membrane damage (Lucio et al, ). Lucio et al () have shown that lipids such as phosphatidylcholine, phosphatidylethanolamine, phosphatidylcholine plasmanyl, phosphatidylcholine plasmenyl and phosphatidic acid might be treated as markers of sperm motility.…”
Section: Structure Of Spermatozoamentioning
confidence: 99%
“…Unfortunately, the presence of double bonds increases the chemical reactivity, which may lead to the loss of motility and membrane damage . Lucio et al (2017) have shown that lipids such as phosphatidylcholine, phosphatidylethanolamine, phosphatidylcholine plasmanyl, phosphatidylcholine plasmenyl and phosphatidic acid might be treated as markers of sperm motility. Different membrane proteins are localized in the plasma membrane of spermatozoa.…”
Section: Matur Ati On Of S Permatozoa In the Epid Idymismentioning
confidence: 99%